Hearts in the lab, hands for the earth: AI bioinformatics in rural education (a phenomenology study) - Magallanes, Edwardo L.; Sari, Wahyu Wido (Proceedings of International Conference on Research in Education, 2025)
This study explored the integration of technology (AI and bioinformatics) in socio-ecological projects as a means of strengthening character values among high school students who enrolled in biotechnology for young learners. These students came from three different schools in Northern Luzon, Philippines. Conducted within a biotechnology enrichment class for young learners, the project encouraged students to address real-world environmental challenges in the rural communities of Tuguegarao, Gataran, and Antipolog in the Northern Philippines. The learning cycle comprised three phases: students were first introduced to innovative technologies and applications; they then investigated issues affecting local rivers and soils; and finally, leveraging AI and related applications, they designed enzymes with potential use in bioremediation. Guided by a qualitative phenomenological approach, this research focused on the lived experience of students for their experienced character development, scientific engagement, and rich personal reflections from students. The observation class, students’ reflection, and the deep interview were compiled and clustered into a coding system with pointers: basic skills on AI and biotech before joining the program, empathy, critical thinking, collaboration, and a sense of social responsibility. Beyond technical skills in AI and bioinformatics, the project fostered empathy, critical thinking, collaboration, and a sense of social responsibility. The findings highlight the potential of technology-based socio-ecological projects not only to enhance scientific literacy but also to cultivate character values essential for human dignity and ecological sustainability. This approach demonstrated how integrating AI-driven biotechnology education with local environmental contexts can empower youth to become ethically grounded innovators in addressing global challenges.